The Oxford handbook of innovation - Fagerberg, Jan.; Mowery, David C.; Nelson, Richard R. (Oxford : Oxford University Press, 2006)
This handbook provides academics and students with a comprehensive and holistic understanding of the phenomenon of innovation.
Originally published: 2005.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Organizational change; Technological innovations; Technological innovations -- Economic aspects